Consumption Culture Online: A Virtual Ethnography Study Of K-Pop Group Order Community - Salsabila, Distria; Sukmono, Filosa Gita (Universitas Islam Negeri Raden Intan Lampung, 2025)
South Korea’s product, K-pop music, is highly popular in Indonesia, making it a part of popular culture. NCT is one of the well-known K-pop boy groups. As a form of loyalty, NCTzens engage in various ways to support NCT, including purchasing merchandise related to their idols. This phenomenon of merchandise consumption has led to the emergence of virtual communities in the form of K-pop Group Orders. This study aims to provide an overview of the cultural consumption of NCT fans through Group Order NCT by Withaechanie on the LINE platform. A qualitative descriptive method with a virtual ethnographic approach is employed, utilizing data collection techniques such as interviews, participant observation, and documentation. The collected data is analyzed based on the four levels of cyber media analysis (AMS). The findings of this study indicate that K-pop Group Orders are not merely economic activities but also serve as spaces for fans to build a collective identity, share information, strengthen their loyalty to idols, and create shared values and norms. Furthermore, this study also discovers the presence of cultural artifacts and an online fan reality interconnected with their real-life (offline) experiences